2021
DOI: 10.3389/fphar.2021.708785
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Impact of Costus (Saussurea lappa) Against Ehrlich Solid Tumor-Induced Cardiac Toxicity and DNA Damage in Female Mice

Abstract: Breast cancer remains the most common cause of cancer deaths among women globally. Ehrlich solid tumor (EST) is a transplantable tumor model for simulating breast cancer. This study aims to describe the protective role of costus (Saussurea lappa) root against EST-induced cardiac toxicity. Forty female mice were randomly and equally divided into four groups (G1, control group; G2, costus group; G3, EST group; G4, EST + costus). The results showed that compared to the control, EST induced a significant increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…Current results are in convention with those found by Hoek et al 42 who identified that NPs affected cardiovascular system inducing not only cardiovascular toxicity and atherosclerosis, but also, increased risk of cardiopulmonary toxicity. In like manner, our findings agree with Elgharabawy et al 16 who reported that costus had a beneficial effect in treatment of cardiac toxicity induced by Ehrlich solid tumor in mice. Correspondingly, CuO NPs toxicity was associated with congestion, infiltration, and even necrosis of heart tissues.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Current results are in convention with those found by Hoek et al 42 who identified that NPs affected cardiovascular system inducing not only cardiovascular toxicity and atherosclerosis, but also, increased risk of cardiopulmonary toxicity. In like manner, our findings agree with Elgharabawy et al 16 who reported that costus had a beneficial effect in treatment of cardiac toxicity induced by Ehrlich solid tumor in mice. Correspondingly, CuO NPs toxicity was associated with congestion, infiltration, and even necrosis of heart tissues.…”
Section: Discussionsupporting
confidence: 93%
“…Determination of serum creatine kinase‐MB (CK‐MB) and creatine kinase enzyme (CPK) levels were estimated using a colorimetric method by Alotaibi et al 1 and Elgharabawy et al, 16 respectively. Serum lactate dehydrogenase (LDH) activity was estimated by a kinetic method using kits (Vitro Scient, Cairo, Egypt) as per Zilva and Pannall 19 and serum myoglobin (Mb) level by the method of Khan et al 20 The activities of both serum aspartate aminotransferase (AST) and alkaline phosphatase (ALP) were estimated using a colorimetric method according to Moustafa et al 21 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This ensures blood supply to the newly proliferative cancer cells and enhances the generation and stabilization of cancer stem cells [ 74 , 75 , 76 ]. Previous studies disclosed the angiogenic capabilities of VEGF in Ehrlich solid carcinomas, with correlation to the chemotherapeutic efficacy and prognosis of the tested drug [ 77 , 78 , 79 , 80 ]. Herein, DOX-PRNP2 ameliorated the elevated tumor levels of IL-6, TNF-α and VEGF more efficiently than free DOX.…”
Section: Discussionmentioning
confidence: 99%